Lack of an Exposure Response and Interaction With HLA-DPβ1 and DRβ1 Polymorphisms in the Development of Beryllium Toxicity in a High Beryllium Exposure Cohort. Issue 1 (January 2020) - Widyaningsih, Vitri; Rosenman, Kenneth; Reilly, Mary Jo; Wang, Ling; Pathak, Dorothy R.; Gardiner, Joseph C.; Rice, Carol; Monos, Dimitri; Rossman, Milton
Abstract : Objective: To evaluate interaction of HLA-DPβ1 and DRβ1 polymorphisms with metrics of beryllium exposure, in the development of beryllium sensitization (BeS) and chronic beryllium disease (CBD). Methods: A matched case-control study of 61 CBD, 41 BeS, and 259 controls from two beryllium-processing facilities. Results: BES and CBD were significantly associated with presence of DPβE69. Dose response of exposure was not observed for the development of BES and CBD with/without adjustment for DPβE69 ( P > 0.05). The DRβE71 polymorphism was more common in BeS than CBD after adjusting for exposure and maybe a protective factor (aOR 0.4, 95% CI 0.2 to 0.9) against the progression of BeS to CBD. Conclusion: No exposure–response association was found, which may reflect that the workers in this high exposure cohort were above a threshold level where an exposure–response could be observed. Abstract : Supplemental Digital Content is available in the text